The first transition metal phthalocyanines: sensitizing rubrene emission based on triplet–triplet annihilation. Issue 9 (26th June 2017) - Han, Jianlei; Zhang, Fei; You, Jing; Hiroaki, Yonemura; Yamada, Sunao; Morifuji, Toru; Wang, Shirong; Li, Xianggao
Abstract : Metallophthalocyanines with transition elements are applied to sensitize Rubrene in TTA-PUC system. The TTA-PUC system with fourth period metals showed even higher Φ PUC than PtPc-o-Cou in same conditions. Abstract : Metallophthalocyanines (MPc-o-Cou, M = Fe, Co, Ni, and Cu) with fourth period metal ions have been successfully applied as a sensitizer coupled with rubrene (Rub) in photon upconversion based on triplet–triplet annihilation. An upconversion quantum yield ( ϕ PUC ) of up to 4.82% was observed in the CoPc-o-Cou : Rub couple. The absorption and phosphorescence emission spectra showed that the Q bands and phosphorescence emission peaks were dramatically dependent on the number of d-electrons of the metal ions in MPc-o-Cou. These results suggested that the photon upconversion behavior of MPc-o-Cou : Rub systems could be managed by altering the metal ions in MPc-o-Cou.